GREEN ENTREPRENEURSHIP FOR A SUSTAINABLE FUTURE: A BIBLIOMETRIC ANALYSIS (Third Sector Social Economic Review, 2024)
Green entrepreneurship refers to the application of the entrepreneurial process to establish enterprises that address environmental issues, have a strong environmental consciousness, and operate in a sustainable manner. This topic has been extensively examined in recent years in academic research. Green entrepreneurship refers to the process of creating and executing company strategies, products, and services that are designed to be ecologically sustainable. Green entrepreneurship is a powerful catalyst for promoting positive transformation by integrating ecological accountability with economic sustainability.The academic literature on green entrepreneurship, encompassing diverse facets of sustainable company, is now in a nascent stage and necessitates field analysis. The objective of this study is to assess the characteristics of publications in the global literature on green entrepreneurship using bibliometric analysis. This analysis will help identify important research areas and provide insights for future research paths. To accomplish this objective, we analyzed publications in the Web of Science database and then using Vosviewer software to visualize the collected data. ""Business Strategy and The Environment"" has the highest amount of publications on green entrepreneurship, according to the research. Jeffrey G. York is the most prolific researcher in terms of the amount of articles on the subject. Dean (2007) holds the record for receiving the highest number of citations for an article he authored. Based on co-citation analysis, Schaltegger (2002) was the researcher who received the highest number of citations. Upon closer examination of the studies, it becomes evident that green entrepreneurship is primarily linked to creativity, innovation, sustainability, and sustainable entrepreneurship. The research findings highlight the crucial aspects involved in the growth of green entrepreneurship and the factors that influence it. This research is expected to provide guidance to scholars and businesses who are interested in the subject, helping them to shape a future that is more sustainable.
Keywords: Entrepreneursip; Green Entrepreneurship; Ecopreneurship; Environmental Entrepreneurship; Bibliometric Analysis